Translation, cultural adaptation and validation of the facial disability index into Brazilian Portuguese - Graciano,Agnaldo J. (2020)
Abstract Introduction: Facial paralysis may occur due to a variety of causes. It is associated to the impairment of some basic daily activities such as eating, drinking, speaking and social communication, which affects the quality of life of these patients. The facial disability index is a short form auto reported outcome questionnaire used to assess patient with facial paralysis. It has been validated and proved to be superior to other general health related quality of life questionnaires. Objective: We aim to do the cultural adaptation and validate the facial disability index into Brazilian Portuguese. Methods: Translation and cultural-adaptation following the stages recommended by the International Society of Pharmacoeconomics Outcomes Research task force. The questionnaire was administered to 100 patients for evaluation of reliability and validation. Results: The reliability of the Portuguese version of the facial disability index was found to be adequate, with a Cronbach's alfa coefficient of 0.73 for the complete scale. Intra-class correlation was 0.79 (95% CI: 0.71-0.85) and 0.85 (95% CI: 0.78-0.89) for the physical and social well-being subscales. There was a significant correlation between the social well-being subscale of the Portuguese version of the facial disability index and the social function and mental health components of the SF-36. There was also a correlation between the facial disability index and the degree of facial dysfunction according to the House-Brackmann global scale. Conclusion: This adapted version of the facial disability index provides a valid and reliable instrument to assess the physical and psychosocial impact of facial nerve dysfunction in Brazilian-speaking patients.